HUBUNGAN PELAYANAN, WAKTU TUNGGU DAN FASILITAS DENGAN KEPUASAN PASIEN DI BALAI PENGOBATAN PUSKESMAS KEMBARAN 1 - Multri Karani; Kris Linggardini (Jurnal Kesehatan, 2020)
Background : services, waiting times, facilities as an indicator of the quality of health services become a determining factor in the image of health service institutions in the eyes of the community. Objective: to find out the relationship between services, waiting time and facilities with patients satisfaction at PuskesmasKembaran 1. Method: descriptive analytic methods. With cross sectional study, the sampling technique using purpose sampling technique. Result: the result of the study found that those who rated good service were 61 (64.2%) respondent and those who rated poor service were 34 (35.8%) respondents. There are 82 (86.3%) respondents who need a waiting time equal to or less than 60 minutes, and there are 13 (%) respondents who need a waiting time of more than 60 minutes. Those who rated adequate facilities are 67 respondents (70.5%), and those who rated inadequate facilities are 28 respondents (29.5%). Those who rated patient satisfaction in the satisfied category were 29 respondents (30.5%), 53 respondents (55.8%) who rated patient satisfaction in the moderately satisfied category, while 13 respondents (13.7%) who rated patient satisfaction in the less category satisfied. Conclusion: based on the results, it can be conclude that there is a relationship between services, waiting time and facilities with patients satisfaction with p value for each variables are 0.000